ПОВАГА ДО СУДУ І СУДДІ ЯК СОЦІАЛЬНА І ПРАВОВА ЦІННІСТЬ - Коновалова, Надія Тарасівна (SUPREMANCE OF LAW, 2018)
The article explores the theoretical (legal) and practical aspects and presents proposals for determining the essence and meaningful properties of the concept (legal category) of “contempt of court (judge)” in the context of social and legal value. It is proved that respect for court and judge is a legal and social value, which together with public confi dence are the guarantees of the efficiency of the justice system.